Analysis of Dietary Pattern Factors and Hypertension in the Elderly in Bantimurung, Maros Regency - Rahmaniar, Andi; Syafruddin, Syafruddin; Selvia, Selvia; Vitariani, Aisyah; Hasanah, Siti Uswatun (International Journal of Health Sciences, 2023)
The diet that causes hypertension is the diet of the elderly consuming foods that contain sugar, high salt, excessive fat such as thick coconut milk, oil, vegetables and fruit that contain gas, and drinks Which in consumption every day like coffee. This research aims to provide an explanation of the relationship between patterns Eat with incident hypertension on elderly in Bantimurung, Maros Regency. The research method used was cross sectional with sampling techniques Which used were 40 respondents regarding the distribution of respondents based on Low eating patterns with the incidence of hypertension in Bantimurung, Maros Regency, low 0 respondents (0.0%). Moderate diet with the incidence of hypertension, moderate 0 respondents (0.0%). Diet High with incidence hypertension, High 3 respondents (9.7%). Low 4 respondents (66.7%). Moderate diet with the incidence of hypertension, 3 respondents (100%). Diet High with incidence hypertension, Height 20 respondents (64.5%), Then Low 2 respondents (33.3%). Pattern Moderate eating with the incidence of hypertension, Moderate 0 respondents (0.0%). High diet with incident hypertension, Tall 8 respondents (25.8%). The research results obtained showed no relationship between diet and the incidence of hypertension in the elderly is (p = 0.680 < 0.05. This means there is no relationship between pattern Eat with incident hypertension on elderly in Bantimurung, Maros Regency. Conclusions on research on the relationship between eating patterns and events hypertension in the elderly in Bantimurung, Maros Regency, it was concluded that: "There is no relationship between pattern Eat with incident hypertension on elderly in Bantimurung, Maros Regency with p = 0.680”.